Solar flare induced D region perturbation in the ionosphere, as revealed from a short-distance VLF propagation path - Todoroki, Y.; Maekawa, S.; Yamauchi, T.; Horie, T.; Hayakawa, M. (Geophysical research letters, 2007)
Short‐distance (propagation distance less than 1,000 km) VLF subionospheric propagation is, for the first time, used to study the solar flare induced D‐region perturbations of the lower ionosphere. We have used two years data for a propagation path from the Japanese VLF transmitter (call sign JJI, frequency = 22.2 kHz, and located at Ebino, Kyushu) to a receiving station of Chofu, Tokyo. For the sake of comparison, we have also used the long distance VLF path (NWC‐Chofu). First of all, the value of perturbation in amplitude (ΔA) for the short‐distance path seems to be much more enhanced (ΔA = 8∼9 dB) for this short‐path than the long‐distance paths previously studied. The experimental value of ΔA is found to monotonically increase with the logarithm of X‐ray flux. This dependence is numerically simulated by means of the FDTD (finite difference time domain) method to deduce the D‐region perturbation, {1 + C exp {−(z − z0)2/2β2} (C: enhancement factor, z0: reference height and β: vertical extent) (this modification seems to be much more realistic than the previous two parameter modeling in an exponential profile). The numerical computations with z0 ∼60 km and β ∼ 10 km have shown that the value of ΔA increase up to ∼6 dB in a range of X‐ray flux from C = 10 to C = 103. As the conclusion, the ΔA is closely related with the logarithm of solar X‐ray flux, so that we will be able to deduce the C value from the observed ΔA value.